2012
DOI: 10.1002/ajhb.22325
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial volume, cranial thickness, and hyperostosis frontalis interna in the elderly

Abstract: HFI is accompanied by an increase in thickness of all calvarial bones and reduced ICV. In addition, the thickening process initiated by HFI is synchronized among the calvarial bones. Presence of HFI suggests a decrease in brain volume and has a major clinical significance as it may indicate the beginning of degenerative processes of the brain. In addition, as females age, their skulls tend to develop more robust characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Previous studies have hypothesized that with age, the cranial bones thicken as a result of decreased ICV (May et al 2012;Royle et al 2013). The hypothesized mechanism is that the skull compensates for the ICV loss and increases CSF to maintain a relatively constant ICP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have hypothesized that with age, the cranial bones thicken as a result of decreased ICV (May et al 2012;Royle et al 2013). The hypothesized mechanism is that the skull compensates for the ICV loss and increases CSF to maintain a relatively constant ICP.…”
Section: Discussionmentioning
confidence: 99%
“…The significant shape change of the inner frontal region for females may be attributed to a benign physiological condition known as hyperostosis frontalis interna (HFI), which causes a thickening of the skull frontal region. HFI patients are considered to be anatomically normal and are noted as unremarkable in radiology reports (May et al 2010(May et al , 2012Raikos et al 2011). Upon visual inspection of the scans analyzed, 11% of the subjects had changes compatible with HFI, in parallel with estimations of the incidence of HFI in the population (She & Szakacs, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, changes in the ICV must be compensated by parallel changes in other tissues. Interestingly, thickening of the skull was detected in several cases [58,42]. Thus, it is plausible that skull bone thickening is responsible for all, part of, or correlates with, the ICV changes.…”
mentioning
confidence: 99%
“…Recent research has suggested that various symptoms may occur as a consequence of HFI, independent of these syndromes (Attanasio et al 2013;Djonic et al 2016). Specifically, intrusive bone growth in patients with HFI may reduce intracranial volume or compress the cerebral cortex, resulting in various neurological symptoms (May et al 2012). HFI is associated with cognitive slowing, mood disturbance, epilepsy, dementia, schizoaffective disorders, headache and intracranial hypertension (Hershkovitz et al 1999;Devriendt et al 2005;Djonic et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…HFI is associated with cognitive slowing, mood disturbance, epilepsy, dementia, schizoaffective disorders, headache and intracranial hypertension (Hershkovitz et al 1999;Devriendt et al 2005;Djonic et al 2016). In addition there are studies that correlate HFI with Alzheimer's and Parkinson's diseases (May et al 2012;Cetiner Batun et al 2015).…”
Section: Introductionmentioning
confidence: 99%